Endocannabinoid Receptors Gene Expression in Morbidly Obese Women with Nonalcoholic Fatty Liver Disease. (23rd April 2014) - Auguet, Teresa; Berlanga, Alba; Guiu-Jurado, Esther; Terra, Ximena; Martinez, Salomé; Aguilar, Carmen; Filiu, Elisa; Alibalic, Ajla; Sabench, Fàtima; Hernández, Mercé; Del Castillo, Daniel; Richart, Cristóbal
Abstract : Background . Recent reports suggest a role for the endocannabinoid system in the pathology of nonalcoholic fatty liver disease (NAFLD). The aim of this study was to investigate the relationship between liver expression of cannabinoid (CB) receptor subtypes, CB1 and CB2, in morbidly obese (MO) women with different histological stages of NAFLD. Methods . We analysed hepatic CB1 and CB2 mRNA expression, and the expression of genes involved in lipid metabolism in 72 MO women, subclassified by liver histology into MO with normal liver (NL, n = 16 ), simple steatosis (SS, n = 28 ), and nonalcoholic steatohepatitis (NASH, n = 28 ) by enzyme-linked immunosorbent assay and RT-PCR. Results . We found that CB1 mRNA expression was significantly higher in NASH compared with SS and correlated negatively with PPAR α . Regarding CB2, CB2 mRNA expression correlated positively with ACC1, PPAR γ, IL6, TNF α, resistin, and adiponectin. Conclusions . The increased expression of CB1 in NASH and the negative correlation with PPAR α suggest a deleterious role of CB1 in NAFLD. Regarding CB2, its positive correlation with the anti-inflammatory molecule adiponectin and, paradoxically, with inflammatory genes suggests that this receptor has a dual role. Taken together, our results suggest that endocannabinoid receptors might be involved in the pathogenesis of NAFLD, a finding which justifies further study.